Multifunctional Linear Induction Electric Drives - Poška, A.; Savickienė, Z.; Zubaitis, J. (Elektronika ir Elektrotechnika, 2005)
A damper of automatic dosator bunker with multifunctional linear induction electric drive is investigated. The functions of this damper are: dosing of dry materials, shaking off the dust from the bunker walls and localization of the dust explosions. The third function is realized only in emergency case. The structural schematic of the algorithm for this damper computer control and dynamical model of dosator bunker are presented and obtained dynamical characteristics of this automatic dosation system for dry materials are analyzed. Properties of linear induction electric drives give an opportunity to create multifunctional equipment using simple appliance. The force, produced by LAM, can be adjusted using a different winding connection mode (parallel, serial or single) of the electrically and magnetically double-sided linear induction electric motor. Ill. 8, bibl. 6 (in Lithuanian; summaries in Lithuanian, English and Russian).